Drug-Related Problems and Associated Factors among Patients Admitted with Chronic Kidney Disease at Jimma University Medical Center, Jimma Zone, Jimma, Southwest Ethiopia: A Hospital-Based Prospective Observational Study - Aster Wakjira Garedow; Eshetu Mulisa Bobasa; Amare Desalegn Wolide; Fantu Kerga Dibaba; Fanta Gashe Fufa; Birtukan Idilu Tufa; Serkadis Debalke; Kabaye Kumela Goro (International Journal of Nephrology, 2019)
Background. There is an alarming rise of chronic kidney disease prevalence globally associated with significant morbidity and mortality necessitating special attention as one of the major growing public health problems. Medication-related problems are common in hospitalized patients including chronic kidney disease and may lead to increase hospital stay and health care cost and augment the risk of morbidity and mortality. Objective. To determine prevalence of medication-related problems and associated factors among chronic kidney disease patients admitted to Jimma University Medical Center from April to September 2018. Methods. A hospital-based prospective observational study was conducted among 103 chronic kidney disease patients admitted to Jimma University Medical Center from April to September 2018. Data regarding patient characteristics, medications, diagnosis, length of hospitalization, and laboratory results were collected through review of patients’ medical charts. Data were analyzed by using Statistical Package for the Social Sciences (SPSS) version 21.0. Univariate and multivariate logistic regression was utilized to assess the associations between dependent and independent variables. Statistical significance was considered at p value <0.05. Results. Out of 103 chronic kidney disease patients, 81 (78.6%) of patients had MDRs, on average 1.94 ± 0.873 per patient. The rate of overall MRPs was 30.95 per 100 medication orders. The most common MRPs among CKD patients were need additional drug therapy (62 (31%)), nonadherence (40 (20%)), and dose too low (36 (18%)). The most common cause of need additional drug therapy (52 (26%)) was untreated medical conditions; nonadherence (19 (9.5%)) was mostly due to that the patient/caregiver forgets to take/give the medication, and dose too low (29 (14.5%)) was mostly due to that the dose is too low to produce the desired response. Polypharmacy (AOR = 4.695, 95% CI: 1.370–16.091), number of comorbidities (AOR = 3.616, 95% CI: 1.015–1.8741), and stage of CKD (AOR = 3.941, 95% CI: 1.221–12.715) were independent predictors for MRPs. Conclusions. We have demonstrated that medication-related problems are high among chronic kidney disease patients. Marital statuses, stage of CKD, polypharmacy, and comorbidity were independent predictors for MRPs. Interdisciplinary health professionals should work to decrease the high prevalence of MRPs among chronic kidney disease patients.